The creation of APP , investment in road infrastructure and their economic, social and environmental impacts (2016)
While the construction of roads fourth generation benefits the country's economic growing, we must also analyze the impact that the management of these works generate in the municipalities an environmental social level. These impacts can be positive as employment generation or negative as the involvement of the Ecosystem among many others that will be addressed throughout this article.